Analisis Hukum tentang Pelanggaran Hak Atas Tanah dalam Kasus Perampasan Tanah di Indonesia - Attar Yafiq; Coman Labis (Jurnal Teknik dan Teknologi Indonesia, 2023)
As an organization engaged in the mining sales sector and in line with the rapid economic development in Indonesia, the sales sector is also growing rapidly over time. In an effort to regulate the quality of mining in Indonesia, the government has issued policies in the form of provisions and legislation. Law regarding mineral and coal mining No.4 of 2009 along with government regulation No.23 of 2010.